Comparative performance analysis of mixed halide perovskite solar cells with different transport layers and back metal contacts. (4th May 2021) - Jayan, K Deepthi; Sebastian, Varkey
Abstract: In this study, SCAPS-1D software is used to model and analyze the performance of various perovskite solar cells (PSCs) with diverse back contact metals, electron transport layers and hole transport layers combined with different mixed halide perovskite absorber materials CH3 NH3 PbI3− X Cl X and CH3 NH3 PbI3− X Br X for X = 1, 2. With CH3 NH3 PbI3− X Cl X as the absorber layer, the best performance is obtained for the configuration glass/fluorine-doped tin oxide (FTO)/indium gallium zinc oxide (IGZO)/CH3 NH3 PbI3− X Cl X /CuSbS2 /Au for X = 1 with a fill factor (FF) of 61.83% and a power conversion efficiency of 13.31%. The device configuration glass/FTO/IGZO/CH3 NH3 PbI3− X Br X /CuO/Pd for X = 1 shows the best performance with a power conversion efficiency of 15.55% and FF of 71.19% for CH3 NH3 PbI3− X Cl X as the absorber layer. The study shows that the optimum total defect density values of the absorber layer, MAPbI3− X Cl X with X = 1 and X = 2 are 2.5 × 10 13 cm −3 and 2.5 × 10 14 cm −3, respectively. For the MAPbI3− X Br X absorber layer, with X = 1 and 2, the optimum defect density is found to be 1 × 10 15 cm −3 . The optimum dopant concentration is found to be 1.0 × 10 18 cm −3 and 1.0 × 10 16 cm −3, respectively, for PSCs with MAPbI3− X ClX as the absorber layer, for X = 1 and 2. For PSCs with MAPbI3– X Br X as an absorber layer with X = 1 and 2, the optimum dopant density is found to be 1.0 × 10 16 cm −3 each. The device is found to be stable at an operating temperature of 300 K.